Does the application of expandable cages in TLIF provide improved clinical and radiological results compared to static cages? A meta-analysis - Lin, Guang-Xun; Kim, Jin-Sung; Kotheeranurak, Vit; Chen, Chien-Min; Hu, Bao-Shan; Rui, Gang (Frontiers in Surgery, 2022)
Purpose: This study aimed to provide a direct meta-analysis of the evidence comparing outcomes between expandable cages and static cages in patients with transforaminal lumbar interbody fusion (TLIF). Methods: A search of relevant materials from databases was performed from inception to March 7, 2022. Clinical and radiological outcomes were included. Results: Ten studies (1440 patients) were included. The anterior disc height and foraminal height for expandable cages were substantially higher than those for static cages at the final follow-up (P < 0.0001; P = 0.05). In comparison with static cages, although not statistically significant, expandable cages showed beneficial results, including an increase in posterior disc height and segmental lordosis. There were no statistically significant differences in segmental lordosis, lumbar lordosis, pelvic parameters, cage subsidence, or fusion rates (P > 0.05). Oswestry disability index scores for expandable cages were substantially lower than those for static cages at the final follow-up (P = 0.0007). Interestingly, although the preoperative visual analog scores for back and leg pain were significantly higher in the expandable group than in the static group (P < 0.0001; P = 0.008), there was no significant difference between the static and expandable groups during the final follow-up (P = 0.51; P = 0.85). Conclusions: Expandable cages are associated with improved functional outcomes and reduced postoperative disc and foraminal heights in patients with TLIF. In addition, no statistically significant differences were observed in segmental lordosis, lumbar lordosis, pelvic parameters, cage subsidence, or fusion rate.